Verification of Cau River biochemical water quality forecasted from local governments’ socioeconomic projections in Bac Kan and Thai Nguyen provinces, Vietnam - Ha, Pham Thi; Villeneuve, Jean-Pierre; Duchesne, Sophie; Hien, Ha Ngoc; Bach, Duong Ngoc (Revue des sciences de l’eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2018)
In this study, we made a verification of water quality between forecasted and monitoring data in 2015 to find out the differences for Cau River water quality, BOD5 concentration (5-day Biochemical Oxygen Demand). Then, an analysis on main development factors which may cause these differences was made. The results showed that in general, BOD5 monitoring concentrations are lower than forecasted median results and meet the standard QCVN 08-MT:2015/BTNMT for surface water quality, while the forecasted concentrations in some periods are over the standard. Local government’ control of population growth in Bac Kan City is considered as one of the major reasons to make Cau River water quality better than forecasted. The statistic population data of Bac Kan City in 2015 is lower than the forecasted population: 26.19% lower than the forecasted in the low population growth scenario (S1), 28.04% in the medium population growth scenario (S2), and 29.8% in the high population growth scenario (S3). Besides, the operation of domestic wastewater treatment plant in Cho Moi Town, which was not considered in developing and assessing the impacts of population scenarios on water quality, is also considered as one of the reasons why the Cau River monitoring water quality (BOD5 concentration) is better than forecasted. This verification result is important and useful for increasing the quality of scenario development and water quality forecast in the future.